TRASH to TREASURE: UTILIZING WASTE MATERIALS AS A MEDIUM of ENGLISH INSTRUCTION - Sondang Pondan Leoanak; Bonik Kurniati Amalo (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2018)
Abstract: It is believed that teaching  and  learning  experiences  that  involve the learner  actively in practical examples are engaged longer than theoretical experiences. Instructional resources are teaching aids or media used to help teachers and students in classroom interaction. These aids help teachers to provide fun, interesting and enjoyable platform (effective presentation) to convey information of a given topic as a means of motivating students to achieve their learning objectives. In general, the present study aims to find out how the teachers in Rijalul  Ghad  Islamic school  in  Kera  island,  Kupang  regency, East Nusa Tenggara  Province, Indonesia utilized waste materials to support their teaching and learning process in the classroom. The data were collected using classroom observation, semi-structured interview with the teachers as well as the students as the respondents and a list 15-item of questions about the level of application in utilizing instructional media addressed to the teachers and the students. This study reveals that the students were active during the application of the instructional media using waste materials such as papers and drinking mineral bottles. In addition, during the application of the teaching and learning aids, the students also learnt how to work in team during group discussion and how to appreciate other’s opinion. However, a support on the use of teaching aids, especially teacher’s made (or teacher-students’ made) need to be increased among teachers. This is because, not all teachers are able to utilize waste materials in to instructional media